The Linguistic Features in the Conversation of Grade Ten Students of SMA Negeri 2 Pematangsiantar - Siagian, Sunaryo (Pascasarjana Universitas HKBP Nommensen, 2022)
This research aimed to describe the linguistic features by male and female in students conversation ofgrade eleven students of SMA Negeri 2 Pematangsiantar. To find out the answer of the problem in thisresearch, the researcher uses the related theories, they are Lakoff (1975), Holmes (2010) and Meyerhoff(2006). The design of this research was descriptive qualitative research. The participants were the gradeeleven of SMA Negeri 2 Pematangsiantar. The researcher used two classes, where one class (26 students)and the other one (36 students) was as the control group. The instrument for collecting the data washandphone. The research‘s results showed that both male and female characters use language featuresproposed by Lakoff (1975), such as, empty adjectives, hedge, intensifier, hypercorrect grammar, superpolite form, tag question, and emphatic stress, even though the characteristics of color words andquestion intonation have not been found in the characters‘ utterances. The difference between men andwomen‘s speeches is shown clearly through the characteristic of hypercorrect grammar in which malestudents used informal speeches in higher frequency than female students and male students intend tolexical hedges and filler in their conversation than female students and also super polite form malestudents seldom to use it or never used it in their conversation and female students used avoidance ofstrong swear words than male students never used it.. Overall, it can be said female students had moreformal language variation, while for male students had more informal language variation.